(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Information technology is a way to change marketing research in India. Despite that, the improvement of Information technology achieves quickly changes and modernization in marketing research. This paper put an effective analysis on role of information technology in marketing.